Analysis of river rehabilitation success, Pipers River, Tasmania. (August 2018) - Tedford, Matthew; Ellison, Joanna C.
Highlights: River geomorphic and hydraulic indicators show long-term benefits of rehabilitation. Long term data shows river stabilization and recovery from channel erosion. Unstable and eroding river reaches recovered after extensive willow removal. Indicators of cross sectional profiles augment water quality and biotic surveys. River rehabilitation by volunteer community groups is beneficial to river values. Abstract: Rivers provide a range of ecosystem services, habitats for rare and endangered species, and water for use by human communities. In the last 200 years, rivers have become degraded by human impacts, necessitating large investments in rehabilitation and restoration, which have been little evaluated for their long term success. Australian rivers have undergone more rapid recent degradation than Europe, and this study assessed change of the Pipers River in Tasmania from 2000 to 2016, during which time the community undertook major rehabilitation efforts, including willow removal, riparian fencing and native vegetation replanting. River hydraulics and channel geomorphology were assessed by comparing channel cross-sectional profiles and hydraulic data from before and after. Historical photographs and site descriptions were assessed for river change, including channel features and vegetation condition. Results demonstrated the resilience of a bedrock confined reach to degradation pressure, and recovery from erosion trajectories at a rehabilitated floodplain reach, with natural vegetation regeneration. Two previously unstable eroding reaches after rehabilitation showed stabilized conditions and hydraulic values, with reduction in turbulent and critical flow. This study demonstrates that catchment rehabilitation activities have a positive effect on stabilizing and recovery from channel erosion. The long term outcomes of river rehabilitation initiatives in reducing channel degradation is little researched previously, and this assessment has shown community investment to be largely successful. This geomorphic and hydraulic evidence contributes to existing understanding from water quality and aquatic biotic surveys, that investment in river rehabilitation has long-term positive benefits.